The social networks and paradoxes of the opt-out movement amid the Common Core State Standards implementation: The case of New York - Yinying Wang (Arizona State University, 2017)
Opting out of state standardized tests has recently become a movement-a series of grassroots, organized efforts to refuse to take high-stakes state standardized tests. In particular, the opt-out rates in the state of New York reached 20% in 2015 and 21% in 2016. This study aims to illustrate the social networks and examine the paradoxes that have propelled the opt-out movement in New York-the movement's epicenter with the highest opt-out rate in the United States. Drawing on the conceptual frameworks of social movement theory, social network theory, and policy paradox, this study compiled the opt-out corpus by using the data from 221 press-coverage and 30 archival documents. Social network analysis was performed by examining the relational data that suggest coalition ties between movement actors. Further, to explicate how the movement actors forged coalition ties, all data in the corpus were then coded by Stone's framework of policy paradox regarding how the movement goals were articulated, how the movement was framed, and what policy solutions were mobilized. In addition to identifying the movement actors and two competing coalitions, it is found that to forge coalition ties, the movement actors in the opposing coalitions articulated contested goals of standardized testing, framed the movement via symbols, numbers, and interests, as well as mobilized policy solutions via inducements, rights, and power. The findings have important and timely implications for policymakers and movement actors as they seek and advance on common ground to make substantive changes in education policy.